Surface properties of chlorophyll-a sensitized TiO2 nanorods for dye-sensitized solar cells applications - Mahadik, Satish A.; Yadav, Hemraj M; Mahadik, Sarika S (Colloid and interface science communications, 2022)
Dye-sensitized solar cells (DSSCs) based on TiO2 nanorods have recently achieved improvement by tuning surface polarity with the help of chlorophyll-a dye. Additionally, we have successfully explored the effects of surface free energy, oxygen defect concentration, micro strain, surface morphology, chemical composition, photoluminescence, and surface properties of chlorophyll-a sensitized TiO2 nanorods. Sensitization on TiO2 nanorods has been tested with photoelectrochemical performance, and the resulting surface shows a superhydrophobicity with CA = 154 ± 30 while oxygen defect is reduced to 2.7228 × 1021 cm−3. The surface free energy has been successfully studied with the help of Owens-Wendt-Rabel-Kaelble (OWRK) and the wetting envelope model. A sensitized system of chlorophyll-a and TiO2 nanorods for the DSSC application presents a maximum of 3.69 times PEC improvement under 1000 W light illumination. Superhydrophobic TiO2 surface fabrication has been achieved with dye sensitization to reduce oxygen defects. [Display omitted] •Superhydrophobicity achieves through surface defects alteration with naturally extracted chlorophyll-A.•The surface free energy calculates with The Owens-Wendt-Rabel-Kaelble (OWRK) model.•Polar components of surface free energy visualize with wetting envelop models.•Importance of superhydrophobicity in electrolyte interaction with the dye-sensitized surface.•A role of surface defects in photoelectrochemical performance.